Service Quality Analysis Of Academic Information Systems (SIAKAD) Siti Khodijah Palembang Health Science High School Using The E-S-Qual Model - Whindy Ovianty; Catur Eri Gunawan; Muhamad Son Muarie (The Future of Education Journal, 2025)
Higher education institutions are increasingly reliant on academic information systems to manage comprehensive academic processes. However, a preliminary survey of several respondents revealed user complaints regarding the service quality of these systems. Further analysis identified a gap between user expectations and perceptions of the service quality of the implemented academic information systems. This study aims to measure the service quality of SIAKAD (Academic Information System) at Siti Khodijah College of Health Sciences using the E-S-Qual model, which incorporates four dimensions: reliability, responsiveness, fulfillment, and efficiency. A quantitative approach was employed through a survey targeting students and lecturers. Data were collected using a questionnaire adapted from the E-S-QUAL (Electronic Service Quality) indicators to evaluate the academic information system’s service quality. The results show that there is a negative gap in all dimensions, which means that service quality has not fully met user expectations. The Efficiency dimension has the largest gap (-1.19), followed by Fulfillment (-1.13) and System Availability (-1.12), while the  dimension has the smallest gap (-1.08). These findings indicate the need for improvement, especially in the aspects of efficiency and fulfillment of service promises to increase user satisfaction. This study provides recommendations for information system managers to make improvements to the service process and conduct periodic evaluations for continuous improvement in service quality.